Asymptotische Entwicklung für unabhängige Zufallsgrößen in falle der stabilen Grenzverteilung - Mitalauskas, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Миталаускас. Асимптотическое разложение для независимых случайных величин, в случае устойчивого предельного распределения A. Mitalauskas. Asymptotinis išdėstymas nepriklausomiems atsitiktiniams dydžiams stabilaus pasiskirstymo atveju